Mitigating the growth of plant pathogenic bacterium, fungi, and nematode by using plant-mediated synthesis of copper oxide nanoparticles (CuO NPs). Issue 1 (2nd January 2023) - Khan, Masudulla; Khan, Azmat Ali; Parveen, Aiman; Min, Kim; Yadav, Virendra Kumar; Khan, Azhar U.; Alam, Mahboob
ABSTRACT : Nanoparticles of copper oxide were synthesized from the Spirodela polyrrhiza (greater duckweed) plant. Ultraviolet spectroscopy absorbance of around 400 nm was used for nanoparticle characterization. The presence of copper and oxygen in the biogenic nanoparticles was analyzed by the EDX technique. Based on scanning, and transmission electron microscopy (SEM and TEM) results, copper oxide nanoparticles (CuO NPs) are evenly distributed and spherical, and their sizes are in the 100 nm range. The synthesized nanoparticles of copper oxide were tested for antibacterial, antifungal, and nematicidal effectiveness against plants pest and pathogens. Antifungal and nematicidal activity against pests and plant pathogens was observed, with fungal mycelium reduced by 45–50% and eggs hatching. The findings suggest that plant-based copper oxide nanoparticles could be a potential source of plant pathogen inhibition. From this study, we concluded that synthesized CuO NPs have the potential to serve as a safer alternative for plant disease management. GRAPHICAL ABSTRACT: UF0001